Louis Desliens, un homme, un métier, une collection, un musée en devenir - Jean-Louis Coudrot (In Situ)
Louis Desliens ((1879-1975), a graduate of the Alfortschool of veterinary medicine, was a practicing veterinarian who devoted his life to research. His research, published as early as 1935, was focused on equine medicine, with a special interest in blood dynamometry. Some years later, it was adapted to human research by Forssmann and Cournand, who received the Nobel Prize in 1956 for their discoveries concerning heart catheterization and pathological changes in the circulatory system. Louis Desliens’ grandson, Michel Desliens, donated the totality of his scientific material, his archives, and his collection to the Musée du Pays Châtillonnais – Trésor de Vix, for the purpose of creating a unique veterinary museum in Europe. The synergies between Desliens’ legacy and the museum’s existing collection are evident. Combined with such important pieces as a crater Greek bronze chariot with parade, sacrified Gallic horses by Vertault, and farrier tools of the 17th century, Desliens’ collection promises to be a showcase for the veterinary profession that will have great appeal to the general public.